HIV Point-of-Care Testing in Canadian Settings: A Scoping Review - Minichiello, Alexa; Swab, Michelle; Chongo, Meck; Marshall, Zack; Gahagan, Jacqueline; Maybank, Allison; Hot, Aurélie; Schwandt, Michael; Gaudry, Sonia; Hurley, Oliver; Asghari, Shabnam (Frontiers in Public Health, 2017)
Background HIV point-of-care testing (POCT) was approved for use in Canada in 2005 and provides important public health benefits by providing rapid screening results rather than sending a blood sample to a laboratory and waiting on test results. Access to test results soon after testing (or during the same visit) is believed to increase the likelihood that individuals will receive their results and improve access to confirmatory testing and linkages to care. This paper reviews the literature on the utilization of HIV POCT across Canadian provinces. Methods We searched OVID Medline, Embase, EBM Reviews, PsycINFO, CINAHL, and 20 electronic grey literature databases. All empirical studies investigating HIV POCT programs in Canada published in French or English were included. Results Searches of academic databases identified a total of 6,091 records. After removing duplicates and screening for eligibility, 27 records were included. Ten studies are peer-reviewed articles, and 17 are grey literature reports. HIV POCT in Canada is both feasible and accepted by Canadians. It is preferred to conventional HIV testing (ranging from 81.1 to 97%), and users are highly satisfied with the testing process (ranging between 96 and 100%). Conclusion The majority of studies demonstrate that HIV POCT is feasible, preferred, and accepted by diverse populations in Canada. Losses to follow-up and linkage rates are also good. However, more research is needed to understand how best to scale up HIV POCT in contexts that currently have very limited or no access to testing.